ANALISA UJI PROGNOSTIK TOTAL KOLESTEROL DAN TRIGLISERIDA SEBAGAI PREDIKTOR KEPARAHAN INFEKSI DENGUE - Iswanto Korompot (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2020)
ANALYSIS OF TOTAL CHOLESTEROL AND TRIGLYCERIDE PROGNOSTIC TEST AS A PREDICTOR OF DENGUE INFECTIONSEVERITY Iswanto Korompot1, Agustin Iskandar2 1Clinical Pathology Residency Program, Faculty of Medicine, Brawijaya University/ Dr. Saiful Anwar County General Hospital, Malang; 2Clinical Pathology Department, Faculty of Medicine, Brawijaya University/ Dr. Saiful Anwar County General Hospital, Malang ABSTRACT Background:In Dengue infection occurs liver damage that exacerbates dengue manifestations. Inflammation due to Dengue infection leads to liver parenchymal lessions,elevated antibody, inflammatory cells and various cytokines that can affect lipid metabolism. Aim:To evaluate the correlation between total cholesterol level and Trigliserida level with degree of dengue infection. Method:This study was an observational analitic study with cross sectional design. The population of this research were pediatric patients with dengue infection who were hospitalized in Syaiful Anwar Hospital Malang from January-July 2017 with positive NS-1 laboratory results and/or positive IgM/IgG antidengue immunoserologic tests. Samples were divided into two groups, non DSS and DSS groups. Subjects measured total cholesterol and triglyceride levels. The data obtained were analyzed with spearman correlation test and continued with regression test to determine the prognostic value of both parameters. Result: There were total 39 samples, 22 DSS samples(56,41%) and 17 non DSS samples(43,59%). The correlation between total cholesterol level and degree of dengue infection was obtained by correlation coefficient(r -0.373), whereas correlation between triglyceride level and dengue infection severity level was(r -0.107). Based on the prognostic tes obtained the results of sensitivity and specificity of 45% and 88% for cholesterol levels while for triglycerides obtained 22.72% and 70.59%. Conclusion and suggestion: Total cholesterol levels have a negative weak correlation with degree of dengue infection, while trilyceride levels have no correlation. Thus Cholesterol levels can be a prognostic marker whereas Trigliserida does not. Suggestion Research continued by involving more research subjects. Key word : Dengue, Total Cholesterol, Triglyceyde, SSD